Evaluasi Kinerja Algoritma AES-128 dan SPECK-128/128 pada Sistem Smart Door Lock Berbasis IoT - Yunita Sari; Galura Muhammad Suranegara (JURIKOM (Jurnal Riset Komputer), 2026)
The Internet of Things (IoT) is increasingly being used in smart home systems, one of which is the Smart Door Lock. However, data communication on IoT devices is vulnerable to network attacks such as sniffing and man-in-the-middle, especially since many devices are still designed with weak security mechanisms. The main issue studied in this research is how to protect RFID data from being easily intercepted, while maintaining efficiency on devices with limited resources. The proposed solution is the implementation of AES-128 and SPECK-128/128 cryptographic algorithms on the MQTT communication protocol using ESP8266 devices. The research was conducted experimentally with 50 measurements for each algorithm, covering encryption and decryption time parameters, memory usage, and encryption effectiveness against sniffing. The results show that AES-128 has stable performance but requires more execution time and memory because its algorithm is complex with many stages. In contrast, SPECK-128/128 is faster and more memory-efficient thanks to its simple ARX-based structure, although its consistency is slightly lower. Sniffing analysis shows that both algorithms are capable of encrypting all packets with 100% security, so that no plaintext data can be read. Thus, this study confirms that there is a trade-off between security and efficiency